Guiding migration of transplanted glial progenitor cells in the injured spinal cord - Yuan, Xiao-bing (Sci Rep, 2016)
Transplantation of glial-restricted progenitors (GRPs) is a promising strategy for generating a supportive environment for axon growth in the injured spinal cord. Here we explored the possibility of producing a migratory stream of GRPs via directional cues to create a supportive pathway for axon regeneration. We found that the axon growth inhibitor chondroitin sulfate proteoglycan (CSPG) strongly inhibited the adhesion and migration of GRPs, an effect that could be modulated by the adhesion molecule laminin. Digesting glycosaminoglycan side chains of CSPG with chondroitinase improved GRP migration on stripes of CSPG printed on cover glass, although GRPs were still responsive to the remaining repulsive signals of CSPG. Of all factors tested, the basic fibroblast growth factor (bFGF) had the most significant effect in promoting the migration of cultured GRPs. When GRPs were transplanted into either normal spinal cord of adult rats or the injury site in a dorsal column hemisection model of spinal cord injury, a population of transplanted cells migrated toward the region that was injected with the lentivirus expressing chondroitinase or bFGF. These findings suggest that removing CSPG-mediated inhibition, in combination with guidance by attractive factors, can be a promising strategy to produce a migratory stream of supportive GRPs.